Archaeology, artifacts and antiquities of the ancient Near East : sites, cultures, and proveniences - Muscarella, Oscar White. (Culture and History of the Ancient Near East, 2013)
Archaeology, Artifacts and Antiquities of the Ancient Near East follows the evolution of the author's scholarly work and interests and is divided into several categories of interrelated fields. The first part deals primarily with excavations and associated artifacts, issues in ancient geography and the identification of ancient sites in northwest Iran, the author's research involving the culture and chronology of the Phrygian capital at Gordion in Anatolia, and the chronology and Iranian cultural relations of a site in the Emirate of Sharjah. Part two is wide-ranging and includes chapters on Aegean and ancient Near Eastern cultural and political interconnections, the role of fibulae in revealing cultural and chronological matters, and the gender-determined usage of parasols and their recognition in excavated contexts. There are also articles specifically concerned with "Plunder Culture" and the forgery of both objects and their alleged proveniences. \'At 1,088 pages, this volume provides a wonderful sample- chosen by Muscarella himself - of forty papers spanning the author's career and many interests...This volume is so rich that it contains something for everyone.\' D.T. Potts, NYU, Bibliotheca Orientalis lxxIII n° 3-4, mei-augustus 2016